2022
DOI: 10.1177/14747049221088011
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Effectiveness of Flirtation Tactics: The Effects of sex, Mating Context and Individual Differences in US and Norwegian Samples

Abstract: Flirting involves various signals communicated between individuals. To attract potential mates, men and women exhibit flirtatious behavior to get the attention of, and potentially elicit sexual or romantic interest from, a desired partner. In this first large, preregistered study of judgement of the effectiveness of flirtation tactics based on Sexual Strategies Theory, we considered the effects of flirter’s (actor) sex and mating contexts in addition to rater's (participant) sex across two cultures, Norway and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…Regarding the sexual history of a potential partner for a friend, we do not expect, based on SST, to find evidence of the traditional SDS for signals of sexual availability (Bendixen & Kennair, 2015;Kennair et al, 2022;Schmitt & Buss, 1996). Instead, we expect a reversed sexual double standard that generalizes to the other domains of sexual behavioral history.…”
Section: Aims and Predictionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding the sexual history of a potential partner for a friend, we do not expect, based on SST, to find evidence of the traditional SDS for signals of sexual availability (Bendixen & Kennair, 2015;Kennair et al, 2022;Schmitt & Buss, 1996). Instead, we expect a reversed sexual double standard that generalizes to the other domains of sexual behavioral history.…”
Section: Aims and Predictionsmentioning
confidence: 72%
“…For example, it would predict that signals of sexual availability (e.g., promiscuity) would be particularly effective (and judged so by others) when used by women in a short-term context because the main constraint for men's reproductive fitness is identifying and mating with sexually available women. There is ample empirical evidence for this across studies and cultures (Bendixen & Kennair, 2015;Fisher et al, 2009;Kennair et al, 2022;Schmitt, 2002;Schmitt & Buss, 1996). Still, a woman's prior promiscuous behavior may alert men who pursue a mate for long-term relationship to the fact that future children might not be sired by himself, resulting in negative appraisals of her as a potential mate for a long-term committed relationship (Buss, 2016).…”
Section: Applying Sexual Strategies Theory To Sexual Double Standardsmentioning
confidence: 99%
“…What happens instead is that her high-value dates, after having had sex with her, move on to the next woman. Research supports that Amanda’s strategy is effective for short-term mating, but works counter to her long-term ambitions (Kennair, Wade, et al, 2022).…”
Section: Dating As Self-harmmentioning
confidence: 99%
“…The fact that modern mating arenas channel so much sexual opportunity to the most attractive men makes casual sex a less-suited entry point for relationships. Kennair, Wade, et al (2022) found that people are aware of this, and perhaps Amanda is too, at some level, but she remains unable sufficiently to separate “to have sex” from a productive pursuit of a pair bond, for which people recommend having fun together, engaging in deep conversations, and spending significant time with each other.…”
Section: A Time Contest Before the First Intercoursementioning
confidence: 99%
“…Flirtul presupune diverse semnale comunicate între indivizi. Pentru a atrage potențial parteneri, bărbații și femeile manifestă comportamente de flirt pentru a atrage atenția și pentru a trezi interesul sexual sau romantic de la partenerul dorit (Kennair et al, 2022).…”
Section: Factori Spațio-temporaliunclassified